Transient dual interface measurement of junction-to-case thermal resistance in AlGaN/GaN HEMT utilizing an improved infrared microscope. (November 2016) - Zhai, Yuwei; Liang, Faguo; Guo, Chunsheng; Liu, Yan
Abstract: The junction-to-case thermal resistance ( R θJC ) of a GaN/AlGaN HEMT is measured by Transient Dual Interface Method (TDIM). Different from other works about TDIM, an improved transient infrared microscope is used to measure the cooling curves, other than the traditional electrical method. Z th curves are used to determine the R θJC following the procedure of JESD51-14. The results demonstrate that the R θJC at 40 W power dissipation are about 0.791 K/W. In order to validate the method, measurements following MIL Std 833 have been done, and the results are consistent with the existing papers. Highlights: The R θJC of a GaN/AlGaN HEMT is measured by TDIM using an improved infrared microscope The R θJC of a GaN/AlGaN HEMT is measured by TDIM using an improved infrared microscope. In the infrared microscope, a NI5122 is used to sample the signal, and the calculation software is developed in LabVIEW. The thermal mapper function has been used to measure accurate channel temperature and correct the R θJC results. Measurements of R θJC following MIL Std 833 had been done. The junction temperature was measured by thermal mapper. Because that the case temperature measured by thermocouple may be lower than the real one, the R θJC would be higher.